2020
DOI: 10.22487/jimut.v3i2.81
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Pelayanan Terhadap Kepuasan Pasien Di Rsud Morowali Kecamatan Bungku Tengah

Abstract: This study aims to determine and analyze the influence of service quality consisting of Physical Evidence, Empathy, Reliability, Responsiveness and Guarantee to patient satisfaction In Morowali District Hospital Central Bungku. The problem in this research is whether the service quality consisting of Physical Evidence, Empathy, Reliability, Responsiveness and Guaranteed simultaneously and partially have a significant effect on patient satisfaction In Morowali District Hospital of central Bungku. Based on that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…The findings of this study corroborate those of Salhuteru (2017), Adriansyah et al (2017), andNursanah et al (2020), who found that service quality has a favorable and substantial effect on satisfaction.…”
Section: Figure 3 Heteroskedasticity Testsupporting
confidence: 91%
“…The findings of this study corroborate those of Salhuteru (2017), Adriansyah et al (2017), andNursanah et al (2020), who found that service quality has a favorable and substantial effect on satisfaction.…”
Section: Figure 3 Heteroskedasticity Testsupporting
confidence: 91%
“…Churiyah (2007) states that service quality, which consists of five dimensions, significantly influences hospital performance. Ardiansyah et al (2017), in their research, that simultaneously service quality has a significant effect on patient satisfaction. Based on the description and previous research, the second hypothesis is formulated as follows.…”
Section: Effect Of Service System On Organizational Performancementioning
confidence: 99%
“…Research conducted by Churiyah (2007) shows that service quality, which consists of five dimensions, significantly influences hospital performance. Ardiansyah et al (2017) found that simultaneously service quality has a significant effect on patient satisfaction. Research conducted by Hanafi et al (2022) showed the influence of job satisfaction and spiritual have an influence on organizational performance (hospital).…”
Section: Introductionmentioning
confidence: 99%
“…Kehandalan (reliability) merupakan kesesuaian antara pelayanan yang diberikan dengan yang dibutuhkan dari waktu ke waktu. Kehandalan juga merupakan kemampuan dalam memberi pelayanan sesuai dengan yang di janjikan secara akurat dan terpercaya (19) (20). kehandalan berkaian dengan memberikan pelayanan seperi yang di janjikan, memberikan layanan tepat waktu dan benar,diagnosis yang di berikan akurat,pelayanan yang tidak berbelit belit, pengobatan dan perawatan yang terampil, serta memberikan pelayanan dengan segera(21) (5).…”
Section: Pengaruh Persepsi Mutu Pelayanan Kehandalan (Reliability) Te...unclassified